Strategi Pengembangan Ekowisata Mangrove di Pesisir Pantai Kertomulyo, Kecamatan Trangkil, Kabupaten Pati - Sirojuddin, Wildan; Suharsono, Suharsono; Alimuddin, Khasan (Mafa Press, 2024)
This research aims to find out the strategy for developing Mangrove ecotourism in the coastal area of Kertomulyo village, Trangkil sub-district, Pati Regency. This research is classified as a type of field research, with a qualitative-descriptive method. The data collection techniques use observation, interviews and documentation. And data analysis using SWOT theory. The results of this research show that the strengths possessed by the organization in carrying out the strategy that has been determined are the availability of applicable laws and regulations, the availability of human resources both in quality and quantity, sufficient availability of supporting facilities and infrastructure, and awareness from the public. The weaknesses that an organization has in implementing the strategy that has been determined can be an obstacle to the success of the strategy, such as: Lack of professionalism of the employee apparatus. Public awareness regarding the implementation of development has not yet accumulated. Accurate data regarding the development that will be implemented is not yet available. There has not been a culture of transparency in budget management and good management. Opportunities or opportunities that an organization has in carrying out a predetermined strategic plan can be supporting factors that will have a positive impact on the success of the strategy, including: The existence of business opportunities. There is development in the business world. The occurrence is cross-sectoral. Increased mobility of goods and services. There is coordination from related agencies. Threats definitely occur in every organization which can be a trigger to increase an organization's efforts and creativity in carrying out planned strategies. Some of the threats in tourism strategies are: High business competition, lack of development of facilities and infrastructure, lack of government role, and lack of attractiveness and uniqueness of tourist attractions.